Plasma cathelicidin and longitudinal lung function in current and former smokers. - Robert M Burkes; Jacquie Astemborski; Allison A Lambert; Todd T Brown; Robert A Wise; Gregory D Kirk; M Bradley Drummond (PLoS ONE, 2019)
Introduction Cathelicidin (also known as LL-37 in humans) is an antimicrobial peptide secreted by epithelial and immune cells and regulated by vitamin D. The immunological roles of cathelicidin make it a putative biomarker to identify individuals at risk for reduced lung function. The objective of this study is to determine potential independent associations between low plasma cathelicidin and longitudinal lung function in current or former smokers without COPD. Methods In a nested analysis of 308 participants from an observational cohort study, plasma cathelicidin and serum 25-hydroxy-vitamin D measurements were obtained at baseline, years three and five. The independent association between lowest quartile cathelicidin (<35 ng/ml) and forced-expiratory-volume-in-1-second (FEV1) at baseline, six and 18 months from each cathelicidin measurement was assessed with generalized estimating equations after adjusting for age, sex, race, smoking status and intensity. The long-term stability of cathelicidin and relationship with vitamin D was evaluated. Results The cohort was 91% African-American, mean age 48.6 years, 32% female, and 81% current smokers. Participants with low cathelicidin were more likely to be female and have lower FEV1. Low cathelicidin was not independently associated with baseline FEV1. There was an independent association between low cathelicidin and reduced FEV1 at six months [-72 ml (95% CI, -140 to -8ml); p = 0.027] and 18 months [-103 ml (95% CI, -180 to -27 ml); p = 0.007]. Cathelicidin was stable over time and not correlated with vitamin D level. Conclusion In current and former smokers with preserved lung function, low cathelicidin is associated with sustained lung function reductions at six and 18 months, suggesting that cathelicidin may be an informative biomarker to predict persistent lung function disparities among at-risk individuals.